Point of Intersection In The Application of The Provision of A Buyer In Good Faith Towards Minangkabau Traditional High Heritage Land - Erwin Radon Ardiyanto; Roni Efendi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
Normatively, Indonesian civil law emphasizes the principle of good faith as stipulated in Article 1338 paragraph (3) of the Civil Code and is reinforced by Article 32 paragraph (2) of Government Regulation Number 24 of 1997 and SEMA Number 7 of 2012 and SEMA Number 4 of 2016. These regulations provide legal protection for buyers in good faith, including in the sale and purchase of customary land. However, in reality (das sein), especially in the case of high heritage land in Minangkabau, tensions arise. Traditionally, high heritage land cannot be bought and sold because it is the property of the clan and is passed down from generation to generation. However, the practice of buying and selling still occurs based on the agreement of some clan members, causing conflict when other clan members refuse and take the case to court. The problem of this research is how to apply legal protection for buyers in good faith of high heritage land when faced with the norm of prohibition of buying and selling according to Minangkabau customary law. The research uses a normative juridical method with an approach of statutory regulations, doctrine, and analysis of judicial practices in West Sumatra. The research findings indicate a point of intersection between the principles of protecting buyers in good faith and protecting high-priority ancestral land. Some judges argued that protecting buyers in good faith should be prioritized for legal certainty, while others emphasized that high-priority ancestral land cannot be transferred absolutely because customary law protection must be upheld. Therefore, resolving disputes over the sale and purchase of high-priority ancestral land requires a balance between positive legal certainty and respect for customary law to achieve substantive justice.